2016
DOI: 10.1109/toh.2016.2550044
|View full text |Cite
|
Sign up to set email alerts
|

A Heuristic Force Model for Haptic Simulation of Nasogastric Tube Insertion Using Fuzzy Logic

Abstract: Nasogastric tube (NGT) placement is an essential clinical skill. The training is conventionally performed on rubber mannequins albeit practical limitations. Computer simulation with haptic feedback can potentially offer a more realistic and accessible training method. However, the complex interactions between the tube and the nasogastric passage make it difficult to model the haptic feedback during NGT placement. In this paper, a fuzzy-logic-based approach is proposed to directly transfer the experience of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Choi et al [98] in their study proposed a reality-based training simulation of tube insertion to facilitate NGT placement and showed that this system provides a new educational tool in order to enhance conventional NGT placement. The same group, in another study, explained a method for developing a computerized NGT placement training method for clinical education [99] Reisenberg et al [100] used a modified Delphi method to create a checklist for education and the assessment of NGT insertion and showed that using a validated checklist could decrease costs and complications while increasing the quality of health care. Binstadt et al [101] used a simulation-based module for integration in emergency departments.…”
Section: Educationmentioning
confidence: 99%
“…Choi et al [98] in their study proposed a reality-based training simulation of tube insertion to facilitate NGT placement and showed that this system provides a new educational tool in order to enhance conventional NGT placement. The same group, in another study, explained a method for developing a computerized NGT placement training method for clinical education [99] Reisenberg et al [100] used a modified Delphi method to create a checklist for education and the assessment of NGT insertion and showed that using a validated checklist could decrease costs and complications while increasing the quality of health care. Binstadt et al [101] used a simulation-based module for integration in emergency departments.…”
Section: Educationmentioning
confidence: 99%
“…Conventionally, NGT insertion techniques are initially practised on low-fidelity mannequins, and subsequently human subjects. The prototype of a virtual reality -(VR-) based and haptic simulator for NGT insertion (Choi, He, Chiang & Deng, 2015;and Choi, He, Chiang, Deng & Qin, 2016) was created to facilitate the education and training of NGT placement for nursing students. The system is equipped with physical makeup of a NGT and human head, and an interactive graphic user interface (GUI) that provides high-fidelity and realistic simulation of tube insertion with unique feedback forces through the built-in haptic device (Picture 1).…”
Section: Introductionmentioning
confidence: 99%